2008
DOI: 10.1111/j.1475-5661.2008.00298.x
|View full text |Cite
|
Sign up to set email alerts
|

Political affects in public space: normative blind‐spots in non‐representational ontologies

Abstract: Recent theoretical debates in human geography have been characterised by a preference for ontological styles of argument. The ontologisation of theory is associated with distinctive claims about rethinking 'the political'. This paper draws on an avowedly 'non-representationalist' philosophical perspective to develop an interpretation of ontology-talk as a genre that provides reasons for certain commitments. This argument is developed with reference to recent accounts of the spatial politics of affect in cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
110
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(116 citation statements)
references
References 62 publications
0
110
0
6
Order By: Relevance
“…In addition, they characterised the intentional manipulation of inter-personal relations, dispositions, affects and atmospheres by Sure Start personnel and, in time, other parents (cf. Thrift 2004, Barnett 2008. This emotion work (Schrock et al 2004) did present multiple versions of caring, but also precipitated many other outcomes.…”
Section: "All You Can Do Is Get the Kettle On": Small Acts Kind Wordsmentioning
confidence: 99%
“…In addition, they characterised the intentional manipulation of inter-personal relations, dispositions, affects and atmospheres by Sure Start personnel and, in time, other parents (cf. Thrift 2004, Barnett 2008. This emotion work (Schrock et al 2004) did present multiple versions of caring, but also precipitated many other outcomes.…”
Section: "All You Can Do Is Get the Kettle On": Small Acts Kind Wordsmentioning
confidence: 99%
“…Barnett, 2008;Korf, 2012;Leys, 2011;Wetherell, 2012Wetherell, , 2013; for a recent discussion of a feminist critique, see also Schurr, 2014). In the following, I focus on three fundamental points of criticism that relate to the concepts presented above, since a full review would exceed this paper's scope.…”
Section: Conceptualising Affective Atmospheresmentioning
confidence: 99%
“…Barnett (2008) arise from this. This account has also suggested that one such 'understanding' would be to identify particular 'environmentalities,' such as by delineating the sensoria such as shopping malls in which they are manifest, and then, on that basis, developing alternative design principles (Healy 2012) to those currently operative.…”
Section: Affect and Contestationary Activismmentioning
confidence: 99%